Assessing the Potentiality of Aerobic Rolling Composter to Hasten Vegetable and Fruit Waste - Fitri Amelia; Eka Yusmaita; Yolli Fernanda; Firma Yulianis; Sherly Rahmayani; Ashekul Islam (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Organic waste is mainly categorized in recent days as household waste and city garbage. To meet eco-friendly waste management, incorrect composter or conventional composting methods do not fulfilling the demands even though sometimes the composting procedure is so lengthy. To speed up the composting process, our research team has developed an aerobic composter using microorganisms, e.g., Trichoderma, Effective Microorganism 4 (EM4), and a combination of Trichoderma. Three different aerobic rolling composters (ARC) were designed to speed up the composting process during the testing stage by employing EM4. It showed a greater reduction in waste height utilizing EM4 on the 15th day (3.8%-17.9%) than the conventional one (2%). In addition, inoculation of EM4 and Trichoderma in combination with EM4 caused a 45% reduction in weight. Thus, the composter (type 3) efficiently decomposes the waste with a shorter composting period.